PENGARUH PUPUK KASGOT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAKCOY (Brassica rapa L.) - Bellandina Dewi Yubilia Kare; Made Sukerta; Cokorda Javandira; Komang Dean Ananda (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
The title of this research is “The Effect of Kasgot Fertilizer on the Growth and Yield of Pakcoy (Brassica rapa L.). Pakcoy is a type of plant that is widely cultivated by farmers today. The stems and leaves are wide and the colors are greener than ordinary mustard greens, making this type of mustard more often used by people in various cooking menus. Mustard pakcoy is a plant from the Brassicaceae family that is in great demand because it contains protein, fat, Ca, P, Fe, Vitamins A, B, C, E and K which are very good for health, have high nutritional content, have good prospects of being of high economic value. This research was carried out in the Rebo Ijo garden, Jalan Merdeka IX no. 91, Sumerta Kelod, East Denpasar district from May to June 2022. This study used a Randomized Block Design (RAK) with 6 treatments and 4 replications. The treatment of cassava fertilizer consisted of K1 (25 g) K2 (50 g), K3 (75 g), K4 (100 g), K5 (125 g) K6 (150 g). Each treatment was repeated 4 times so that the total number of treatments became 24 polybags. In the results of this study all parameters of the best yield and that is by offering Kasgot K6 fertilizer (150 g). Presenting Kasgot fertilizer provides the highest plant value, namely plant height speed, number of leaves, leaf area, total fresh weight of plants and total dry weight of plants